Berbagi Pengetahuan adalah Kekuatan: Perspektif Teori Pertukaran Sosial dan Efek Pemediasi Berganda Komitmen Belajar dan Adaptasi Interpersonal - Agustin, Indri Yani; Pradana, Handrio Adhi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This study investigates the mediating effect of learning commitment and interpersonal adaptation on the relationship between knowledge sharing practices and job satisfaction. This study involved 152 respondents, including teaching staff and education staff at Universitas Islam Indonesia. The sampling technique was carried out purposively based on tenure and employment status categorisation. Since the model is a regression analysis with multiple mediations, the mediating effect was examined using Hayes's PROCESS technique. The results found that sharing knowledge practices positively and significantly impacted job satisfaction. They were learning commitment and interpersonal adaptation succeeded in multiple mediating effects on the relationship between knowledge sharing practices and satisfaction. Theoretical and practical contributions are also discussed in this paper.